A chitosan/dextran-based hydrogel as a delivery vehicle of human bone-marrow derived mesenchymal stem cells. (7th June 2017) - Nelson, Vicky J; Dinnunhan, M F K; Turner, Paul R; Faed, Jim M; Cabral, Jaydee D
Abstract: A chitosan/dextran-based (CD) injectable, surgical hydrogel has been developed and shown to be an effective post-operative aid in prevention of scar tissue formation in vivo . The CD hydrogel's effectiveness in a surgical setting prompted an investigation into its capacity as a potential delivery vehicle for bone marrow derived mesenchymal stem cells (BM-MSCs) for regenerative wound healing applications. By housing BM-MSCs within a biocompatible, injectable, hydrogel matrix, viability and protection in cultivation, as well as direct delivery to the damaged site in the host tissue may be achieved. In vitro BM-MSC cell viability in the presence of CD hydrogel was determined by LIVE/DEAD ® fluoresence staining. Flow cytometry studies revealed expression of a conventional BM-MSC surface marker profile. A colony forming cell assay showed a slight statistically significant decrease in the number of colonies grown in CD hydrogel as compared to control cells. In addition, BM-MSCs in the CD hydrogel were able to successfully differentiate into adipocytes and osteocytes. In summary, the CD hydrogel supports MSC growth and differentiation; and therefore, may be used as a potential stem cell delivery vehicle for regenerative medicine and tissue engineering applications.